1988
DOI: 10.1111/j.1741-6612.1988.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Australian Literature in Social Gerontology: A Content Analysis of Trends Since 1980

Abstract: Australian social gerontology entered a new stage of development in the 1980s with the establishment of a number of research projects and educational programmes. The aim of this paper is to make a systematic review of the recent research literature and identify research achievements and knowledge gaps. A total of 158 research articles published in overseas and Australian academic journals are reviewed in terms of source of publication, author institutional affiliation, content and theoretical orientation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The Australian Journal on Ageing has been identified as the single, major outlet for local research in a recent content analysis of Australian gerontological literature covering the period 1980 to 1987 (Minichiello, Alexander, & Jones, 1988). Incorporation of the findings of that analysis captures not only that journal's contents, but also material published elsewhere; notably, many of the publications from the Ageing and the Family Project are included.…”
Section: Tracing the Development Of Gerontological Knowledgementioning
confidence: 99%
“…The Australian Journal on Ageing has been identified as the single, major outlet for local research in a recent content analysis of Australian gerontological literature covering the period 1980 to 1987 (Minichiello, Alexander, & Jones, 1988). Incorporation of the findings of that analysis captures not only that journal's contents, but also material published elsewhere; notably, many of the publications from the Ageing and the Family Project are included.…”
Section: Tracing the Development Of Gerontological Knowledgementioning
confidence: 99%
“…This saw the emergence of a distinctly social gerontology through a growing volume of research into social and psychological aspects of ageing. However, in a content analysis of scholarly Australian literature in social gerontology from 1980 to 1986, Minichiello et al (1988) found an absence of broader interdisciplinary and collaborative research into ageing. They argued that 'Australian clinicians, psychologists and sociologists have created many little islands of knowledge' (Minichiello et al, 1988: 29) and called for bridges to be built between these to improve research data generated on ageing.…”
Section: An Historical Analysismentioning
confidence: 99%
“…The National Workshop considered the substantial increase in the number of publications in the field since the 1980s (see also Howe, forthcoming Kendig, 1988;Minichiello et al, 1988). The Ageing and the Family Project, the Aged Care Research Group, and a number of individual scholars, were shown to have made important contributions to understanding older people and the processes of growing old in Australian society.…”
Section: Research Issuesmentioning
confidence: 99%